5PSQ-033 Antiviral treatment discontinuation in patients with hepatitis b. Issue 1 (23rd March 2023) - Martinez, E; Corrales, S; Dean, C; Codonal, A; Tardaguila, P; Casarrubios, GI; Miranda, A; Lazaro, A
Abstract : Background and Importance: Studies suggest the safest strategy of treatment discontinuation with nucleos(t)ide analogues (NAs) against hepatitis B virus (HBV), is proposed after loss surface antigen (HBsAg). Evidence supports the possibility of discontinuing NAs in the following situations: Patients with positive e antigen (HBeAg) without cirrhosis: after negativisation of HBV-DNA and HBeAg seroconversion, confirmed in 2 determinations separated by 3-6 months and after NAs at least 12 months. Patients with negative HBeAg, without advanced fibrosis early in treatment: after negativisation of HBV-DNA for at least 3 years and HBsAg clearance (qHBsAg) ≤1000 IU/mL. Aim and Objectives: The objective was to characterise the population in treatment with NAs and analyse patients who met requirements for treatment discontinuation Material and Methods: Cross-sectional, descriptive, retrospective study of patients under active treatment with NAs between August 2020-August 2021. Variables collected: demographic, NAs used, treatment duration and clinical (positive or negative HBeAg, HBeAg seroconversion, HBV-DNA, qHBsAg, degree of hepatic fibrosis, HBsAg loss, virological relapse (RV) (HBV-DNA>2000 IU/ml after treatment discontinuation). Results: We included 50 patients (70% men). Median age was 56 years (IQR: 48-66) and median of treatment duration was 66 months (IQR: 27-108). 62% were treated with tenofovir disoproxil fumarato and 38% with entecavir. 8% of patients had positive HBeAg without seroconversion and without negative HBV-DNA. 92% had negative HBeAg with seroconversion and negative DNA-HBV. 32% of patients had qHBsAg ≤1000 IU/ml, 28% ≥1000 IU/ml and 40% not determined. 30% of patients had advanced fibrosis. In 12% of patients with positive HBsAg, treatment discontinuation could be considered. All of them had HBeAg negative, fibrosis F0-F1 at the beginning of treatment, negative HBV-DNA maintained at least 3 years and qHBsAg≤1000 IU/ml. HBsAg loss occurred in 6% of patients who had not discontinued treatment and 16% of patients had to restart treatment for RV. Conclusion and Relevance: Study population includes patients who meet criteria for treatment discontinuation. Treatment discontinuation requires close follow-up to detect RV. In patients with HBsAg loss, treatment was not discontinued due to advanced fibrosis. References and/or Acknowledgements: Conflict of Interest: No conflict of interest.